2015
DOI: 10.5665/sleep.4898
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Access to Positive Airway Pressure Usage with or without an Initial Financial Incentive Improves Treatment Use in Patients with Obstructive Sleep Apnea

Abstract: Positive airway pressure adherence is significantly improved by giving patients Web access to information about their use of the treatment. Inclusion of a financial incentive in the first week had no additive effect in improving adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 40 publications
0
73
0
1
Order By: Relevance
“…The positive impact of patient involvement in therapy was highlighted in a recent study which showed that providing patients with web-based access to their personal PAP usage data increased device usage in the first week of therapy and over 3 months of follow-up compared with usual care [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of patient involvement in therapy was highlighted in a recent study which showed that providing patients with web-based access to their personal PAP usage data increased device usage in the first week of therapy and over 3 months of follow-up compared with usual care [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Average PAP use was 4.7 ± 3.3 h in the usual care group and 5.9 ± 2.5 and 6.3 ± 2.5 h in the web‐based access to PAP usage groups with and without financial incentive. Functional Outcomes of Sleep Questionnaire (FOSQ) scores at 3 months improved with statistical significance in all three groups, but the change in FOSQ scores of web‐based access to PAP usage groups were not different from the control group . Fox et al .…”
Section: Tm Adherence and Progress Of Cpap‐treated Osa Syndrome Patientsmentioning
confidence: 97%
“…Kuna et al [34] randomized 138 recently diagnosed OSAS patients requiring CPAP, to usual care, usual care with access to CPAP usage, or usual care with access to CPAP usage and a financial incentive. After three months, mean adherence was 4.8 and 5 h/night in the intervention groups vs. 3.8 for usual care ( p < 0.0001).…”
Section: Telemonitoring Of Cpap-treated Obstructive Sleep Apnea Symentioning
confidence: 99%